α-Synuclein Up-regulates Monoamine Oxidase A Expression and Activity via Trans-Acting Transcription Factor 1 - Jia, Congcong; Cheng, Cheng; Li, Tianbai; Chen, Xi; Yang, Yuting; Liu, Xinyao; Li, Song; Le, Weidong (Frontiers in Aging Neuroscience, 2021)
Abnormal α-Synuclein (α-SYN) aggregates are the pathological hallmarks of Parkinson's disease (PD), which may affect dopamine (DA) neuron function and DA metabolism. Monoamine oxidase A (MAOA) is an enzyme located on the outer mitochondrial membrane that catalyzes the oxidative deamination of DA. Both α-SYN and MAOA are associated with PD pathogenesis, suggesting a possible crosstalk between these two molecules. In the present study, we aimed to investigate the potential impacts of α-SYN on MAOA function and further explore the underlying mechanisms. Our study showed that overexpression of α-SYN (both wild-type (WT) and A53T) increased MAOA function via up-regulating its expression without impacting MAOA stability. Overexpression of α-SYNWT or α-SYNA53T enhanced the transcription activity of MAOA promoter region containing the binding sites of cell division cycle associated 7 like (R1, a transcriptional repressor of MAOA) and trans-acting transcription factor 1 (Sp1, a transcription factor of MAOA). Interestingly, α-SYN selectively increased Sp1 expression, thereby enhancing the binding capacity of Sp1 with MAOA promoter to increase MAOA expression. Taken together, our findings demonstrate that α-SYN can up-regulate MAOA expression via modulation of Sp1 and may shed light to future studies of α-SYN associated PD pathogenesis.